The Effect Of Family Satisfaction And Job Satisfaction On Quality Of Work Life Of Employees At PT.DEPO PELITA SOKARAJA - Andini, Melli (LPPJPHKI Universitas Dehasen Bengkulu, 2025)
This study aims to examine the effect of family satisfaction and job satisfaction on the quality of work life of employees at PT. Depo Pelita Sokaraja.This research used quantitative research methods and measured instruments using SmartPLS version 4. This study used data collection technique, namely questionnaires. This study used non-probability sampling technique, namely purposive sampling with the criteria of employees who are married and have worked for at least one year. Determination of the sample size in this study used the Slovin formula. Based on the Slovin formula, the sample size in this study was 110 respondents.The results showed that family satisfaction and job satisfaction had a positive and significant effect on the quality of work life of employees at PT. Depo Pelita Sokaraja.